IGF1 Receptor Signaling Regulates Adaptive Radioprotection in Glioma Stem Cells123. (20th March 2013) - Osuka, Satoru; Sampetrean, Oltea; Shimizu, Takatsune; Saga, Isako; Onishi, Nobuyuki; Sugihara, Eiji; Okubo, Jun; Fujita, Satoshi; Takano, Shingo; Matsumura, Akira; Saya, Hideyuki
Abstract Cancer stem cells (CSCs) play an important role in disease recurrence after radiation treatment as a result of intrinsic properties such as high DNA repair capability and antioxidative capacity. It is unclear, however, how CSCs further adapt to escape the toxicity of the repeated irradiation regimens used in clinical practice. Here, we have exposed a population of murine glioma stem cells (GSCs) to fractionated radiation in order to investigate the associated adaptive changes, with the ultimate goal of identifying a targetable factor that regulates acquired radioresistance. We have shown that fractionated radiation induces an increase in IGF1 secretion and a gradual upregulation of the IGF type 1 receptor (IGF1R) in GSCs. Interestingly, IGF1R upregulation exerts a dual radioprotective effect. In the resting state, continuous IGF1 stimulation ultimately induces downregulation of Akt/extracellular‐signal‐regulated kinases (ERK) and FoxO3a activation, which results in slower proliferation and enhanced self‐renewal. In contrast, after acute radiation, the abundance of IGF1R and increased secretion of IGF1 promote a rapid shift from a latent state toward activation of Akt survival signaling, protecting GSCs from radiation toxicity. Treatment of tumors formed by the radioresistant GSCs with an IGF1R inhibitor resulted in a marked increase in radiosensitivity, suggesting that blockade of IGF1R signaling is an effective strategy to reverse radioresistance. Together, our results show that GSCs evade the damage of repeated radiation not only through innate properties but also through gradual inducement of resistance pathways and identify the dynamic regulation of GSCs by IGF1R signaling as a novel mechanism of adaptive radioprotection. STEM CELLS2013;31:627–640